Trick or treat? Pollinator attraction in Vanilla pompona (Orchidaceae). (15th November 2021) - Watteyn, Charlotte; Scaccabarozzi, Daniela; Muys, Bart; Van Der Schueren, Nele; Van Meerbeek, Koenraad; Guizar Amador, Maria F.; Ackerman, James D.; Cedeño Fonseca, Marco V.; Chinchilla Alvarado, Isler F.; Reubens, Bert; Pillco Huarcaya, Ruthmery; Cozzolino, Salvatore; et al.
Abstract: Natural pollination of Vanilla species remains poorly understood. Our research aimed at better understanding the pollinator attraction mechanism of the Neotropical species Vanilla pompona . Based on our results, we hypothesize that the identified pollinator Eulaema cingulata is attracted via a dual mechanism combining floral fragrance rewards and food deception. Abstract in Spanish is available with online material. Abstract : Natural pollination of Vanilla species remains poorly understood. Our research aimed at better understanding the pollinator attraction mechanism of the Neotropical species Vanilla pompona. Based on our results, we hypothesize that the identified pollinator Eulaema cingulata is attracted via a dual mechanism combining floral fragrance rewards and food deception. Resumen: La polinización bajo condiciones naturales de las especies de Vanilla sigue siendo poco conocida. Nuestra investigación tiene como objetivo comprender mejor el mecanismo de atracción de polinizadores de la especie Neotropical Vanilla pompona . Con base en los resultados obtenidos, planteamos la hipótesis de que el polinizador, identificado como Eulaema cingulata, es atraído a través de un mecanismo doble que combina la recompensa por medio de fragancias florales y el engaño alimenticio.